KOMPARASI SÉNGGOL SEKAR KAPASINDÉNAN CUCU S. SETIAWATI, YOYOH SETIA ASIH, DAN NENI HAYATI - Rina Dewi Anggana (Paraguna, 2022)
This paper reveals one of the phenomena that exist in the sekar kapasindénan, related to the characteristics of the freedom of the pasindén (singer) in interpreting a song. This freedom causes a variety of interpretations from one singer to another when presenting the same song. To see the diversity, this article was compiled by comparing the sénggol of Cucu S. Setiawati, Yoyoh Setia Asih, and Neni Hayati in presenting the sekar kapasindénan from type of lagu jadi entitled Tablo and type of lagu jalan entitled Sinyur, through qualitative research methods and musical approach. Through the stage of transcribing the form of sénggol as well as analyzing aspects of melody, vocal technique, and the potential for better sound ambitus of each singer in presenting these songs, then it can be said that the three singers seem to be developing, but the main melodic flow in the lagu jadi as well as the standard kenongan and goongan tones in this type of song still feels the same, so it doesn't change the identity of the song. In the presentation of the two types of songs, Cucu S. Setiawati looks consistent in starting the melody of the song on the first beat of the second bar, different from the two comparisons pasindén who tend to start singing the melody early, namely entering the first bar region, this affects the rhythm space used will be narrower, so that the number of notes, note values, and legato values used is not more than the comparison, however, it turns out that the legato and barrel values that she used are more varied. In addition, when facing the tone of kenongan and goongan she wears a certain sénggol which is different and distinctive. In terms of vocal technique, there are several masieup sora techniques that are equally used by those three singers, but there are also some techniques that are only used by one of the three, and based on observations, it was Yoyoh Setiaasih who used reureues the most. Then it can be concluded that it turns out that the voice of the ambitus of Neni Hayati is not wider than that of Yoyoh Setia Asih and Grandson S. Setiawati.